Phase, structural and thermodynamic analysis of nanocrystalline yttrium oxide (Y2O3) for optical applications - S. Surya; Sakthivel Pandurengan; S. Gokul Raj; G. Ramesh Kumar (Results in Physics, 2025)
This research work targets on the production of Nanocrystalline yttrium oxide (Y₂O₃) Quantum Dots (QDs) where Quantum Confinement Effect plays a vital role on account of varying the annealing temperature and focuses on exploring the thermodynamics of the different sized Y₂O₃ Nanocrystalline QDs. Nanocrystalline yttrium oxide (Y₂O₃) was synthesized using a simple, one-step precipitation method and the resulting powder was annealed at various temperatures 500, 750 and 1000 °C. Simultaneous Thermogravimetric analysis and Differential Scanning Calorimetry (TG-DSC) analysis were performed to monitor the phase transformation of the Y₂O₃ nanoparticles (NPs) from amorphous to crystalline states. By varying the heating rates (5, 10, 15, and 20 °C/min), the activation energy for crystallization was calculated using kinetic models such as Kissinger and Ozawa. Powder X-ray diffraction (XRD) analysis confirmed the formation of single-phase Y₂O₃ nanoparticles in which the annealed samples exhibited a cubic structure corresponding to the Ia3 space group, in good agreement with the standard JCPDS pattern No. 41-1105. Annealing to higher temperatures led to an increase in crystallite size, which was estimated using the Scherrer formula to range between 5 to 12 nm in which the annealed Y₂O₃ nanoparticles at 500 °C shows the least crystallite size of 5 nm. The micro strain (ε), arising from thermal expansion and contraction, was evaluated using the Williamson–Hall (W–H) plot. UV–Visible absorption spectroscopy revealed good transparency in the UV–Vis region; using the absorption coefficient (α), the Tauc’s plot indicated a wide band gap for the material. Photoluminescence (PL) analysis were carried out for asprepared and annealed samples which shows that the emission intensity increase with respect to the increase in annealing temperature. Additionally, Fourier-transform infrared (FTIR) spectroscopy and X-ray photoelectron spectroscopy (XPS) were employed to study the chemical bonding and oxidation states of the Y₂O₃ nanoparticles, respectively. The morphology and the size of the synthesized as prepared samples and the samples annealed at various calcination temperatures were visualized using Scanning electron microscope (SEM) and Transmission electron microscope (TEM) and the results were discussed in detailed